Chemotherapy and cognitive function: comprehensive review on methotrexate‐induced chemobrain - Nadine C. Sabry; Haidy E. Michel; Esther T. Menze (Archives of Pharmaceutical Sciences Ain Shams University)
Chemobrain is a critical life-threatening condition that cancer patients can face during or after chemotherapy. It affects many aspects of the patient’s cognitive ability and it appears as defect in the cancer survivor’s memory or concentration. The learning capacity, attention and executive function can also be influenced. The majority of the time, it manifests subtly and causes momentary, short-term effects. However, a variety of chemotherapeutic drugs adversely affect the quality of life of patients. Continuous, long-term cognitive adverse effects in specific circumstances can emerge from the chemotherapy regimen whether prescribed as monotherapy or as an element in therapeutic plans. This review is deliberated to highlight the mechanisms behind the pathophysiology of chemobrain, with concentration on the cytotoxic agent ‘’methotrexate’’(MTX), which has been revealed to be involved in arduous neurotoxicity. MTX is considered a folate antagonist. It was initially employed for treating different cancer types as well as several anti-inflammatory and/ or immunological disorders. This review is deliberated to highlight the potential pathways responsible for MTX neurotoxicity. Furthermore, the evaluation of the cognitive impairment, detected either in human or in animal models after chemotherapy, is one of the main topics of interest adopted in this article. The likely pharmacotherapeutic interventions and different behavioral tests are also discussed.